PS2-21: Explanation to Understanding: Practices of the Highest Performing Physicians by Patient Survey - Janisse, Tom (Marshfield Clinic, 2011)
BACKGROUND: The MD-Patient Communication Study aims were the best practice communication behaviors of physicians during outpatient clinic visits; and to collect physician perspectives of communication behaviors. Researchers have consistently found the top predictors of overall patient satisfaction are quality of the physician-patient relationship and contributing communications. There is limited understanding however, of the range of specific behaviors in the interaction associated with positive and negative patient perceptions and reactions. METHODS: In phase 1, we conducted a naturalistic, observational study of fifty-five, Permanente Primary Care physician-patient visits using videotape recordings, and incorporating patient and physician reactions to the tape. The physicians, who practiced in Los Angeles and Honolulu, spanned the three strata of high, medium, and low historical patient satisfaction scores. In phase 2, a standardized six-question set was posed, in semi-structured, 60-minute interviews, to 77 of the highest-performing physicians on this patient survey, including: 20 of the highest performers (top 5%) from the LA and Honolulu groups; and 42 and 15, respectively, of the highest performing physicians in Portland and Oakland. These interviews were audio taped with permission, transcribed and coded for patterns. RESULTS: Explanation to achieve understanding was the most commonly cited activity in answer to a ‘physicians’ role in their patients’ healing,’ and in what constitutes a “therapeutic moment in the visit.’ Pattern dimensions include: context – trust, relationship; communication – connection, dialogue; content – visual explanation; role – patient ownership; and support – reassurance, encouragement. Representative verbatims: “It’s how the information is interpreted and packaged, and what’s emphasized, and how it’s customized to the individual;” “I spend a fair amount of time explaining physiology in their terms so they understand why we’re doing what we’re doing, or what’s happening and what to expect;” “If you don’t have a relationship with your patient, then you don’t have a really effective treatment protocol.” CONCLUSIONS: With national health care reform’s new Prevention Codes calling for “Discussion,” and patients’ dependence on explanation to understand and follow through with treatment recommendations, describing how high performing physicians create high patient satisfaction, is of great importance.